2015
DOI: 10.1097/jcn.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Sleep Problems in Patients With Heart Failure and Associations to Rehospitalizations

Abstract: One-third of HF patients with sleep problems at discharge experienced persistent sleep problems at follow-up. Continued sleep problems were associated with all-cause and cardiovascular rehospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
4
14
0
1
Order By: Relevance
“…After controlling for factors associated with survival in heart failure, we found that poor sleepers were 2.5 times more likely to have a cardiac event than were good sleepers. Similar findings were observed in 2 previous studies 5,20 in which self-reported sleep measures were used to examine the relationship between sleep states and prognosis in patients with heart failure. However, these 2 studies 5,20 had some methodological issues.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…After controlling for factors associated with survival in heart failure, we found that poor sleepers were 2.5 times more likely to have a cardiac event than were good sleepers. Similar findings were observed in 2 previous studies 5,20 in which self-reported sleep measures were used to examine the relationship between sleep states and prognosis in patients with heart failure. However, these 2 studies 5,20 had some methodological issues.…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3][4] Sleep disturbance is a common finding among patients with heart failure, [2][3][4] and up to 94% of patients with heart failure experienced sleep disturbance, from occasionally to almost constantly. 4 In a study in which patients with heart failure were followed up for 1 year after discharge from the hospital, Johansson et al 5 found that sleep disturbance was persistent in 30% of the patients who reported sleep problems at discharge and that sleep disturbance newly occurred in 14% of patients who did not report sleep problems at discharge. Several factors contributing to sleep disturbance in patients with heart failure have been identified, including nocturnal dyspnea, comorbid conditions (eg, chronic obstructive pulmonary disease), sleep-disordered breathing, and medications (eg, -blockers).…”
mentioning
confidence: 99%
“…heart failure found higher rates of sleep disturbances than in the general population, and their findings (40%-45%) are more consistent with the findings here, [29][30][31] highlighting the importance of assessing sleep and addressing sleep problems in cardiac rehabilitation efforts. The effect of essential oil inhalation on PSQI scores was substantial in this study (effect size: d = 1).…”
Section: Mcdonnell and Newcombsupporting
confidence: 88%
“…Fatigue and sleep quality seems may create a vicious circle in HF and can adversely affect the outcome, therefore, continuous assessment of sleep should be a part of the clinical routine in the management of HF patients (Johansson et al, 2015) and should not be undervalued (Gau et al, 2011). Identification of sleep quality, however, tend to be ignored (Nasir et al, 2015).…”
Section: Introductionmentioning
confidence: 99%